Teknik Dekontaminasi Cemaran Bakteri pada Karkas dan Daging - Sri Raharjo (agriTECH, 1999)
The exposed surface of hide, hair, feather, and skin accumulate dust, dirt, and fecal materials which is the primary source of bacterial contamination during slaughter. Meat contact surfaces and those associated with personnel, equipment and slaughtering utensils are also frequently considered to be significant sources of meat contamination. Various techniques have been proposed to decontaminate bacteria during meat and poultry processing. The ideal decontamination method should not change appearance, smell, taste or nutritional properties; leave no residues; pose no threat to the environment; cheap and convenient to use; and effectively inactivate or eliminate microorganisms. The existing publications suggest that most the decontamination methods did not affect the smell and taste of the meat or carcasses, except slight acidic taste and smell were noticeable when high concentration of organic acids were used. Transitory changes on appearance were obvious when steam or hot water dip and microwave were used to decontaminate meat and poultry. All of the decontamination method presented here had no significant effect on its nutritional value. The use of higher concentration of chemicals tend to leave objectionable residues. Although they are very effective bactericides, the use of radioactive materials and chemicals should be strictly controlled to minimize their negative effect to the environment. It seems that the use of high pressure water spray in combination with mild concentration of organic acids or ozone may become economically and environmentally acceptable alternatives for meat and poultry decontamination.